(untitled) (Proceeding of SINERGY, 2026)
Such research has the purpose of analyzing the impact of the council characteristics also the ownership structure in dividend policy towards Indonesia. The population consists of 128 consumer non-cyclicals sector business organizations listed on the Indonesian Stock Exchange for the time 2021-2024. The mechanism used in research to take specimens is purposive sampling with a final taste of 69 business institutions and 276 observations. Then analysis the procedure in which it is carried out balanced panel data regrestion together a fixed effect model (FEM) thru Eviews 13. The dependent variable, namely dividend policy, was measured using the dividend payout ratio (DPR). Dependent variable, namely board characteristics, were proxied by board size, board gender, board meetings, also ownership structure consisting of institutional, managerial, also foreign ownership. Then control variable are firm measure and leverage. Research findings show that institutional ownership has a positive impact on dividend policy. Conversely, board size, board gender, board meetings, managerial ownership, also foreign ownership has no impact in dividend policy. This study enriches literacy regarding functions board characteristics and ownership structure at determining dividend policy. Empirically, these findings show that board characteristics are not yet sufficient to determine dividend policy, while ownership structure needs attention because it by now proven so impact the current function improving dividend policy.